The Determinants of Economic Growth in European Regions - Jesus Crespo-Cuaresma; Gernot Doppelhofer; Martin Feldkircher (The Vienna Institute for International Economic Studies (wiiw), 2009)
We use Bayesian Model Averaging (BMA) to evaluate the robustness of determinants of economic growth in a new dataset of 255 European regions in the period 1995-2005. We use three different specifications based on (i) the cross-section of regions, (ii) the cross-section of regions with country fixed effects, and (iii) the cross-section of regions with a spatial autoregressive (SAR) structure. Our results indicate that the income convergence process between countries is dominated by the catching-up process of regions in Central and Eastern Europe (CEE), whereas convergence within countries is mostly a characteristic of regions in old EU member states. We find robust evidence of asymmetric growth performance within countries, with a growth bonus in regions containing capital cities which is particularly sizeable in CEE countries, as well as a robust positive effect of education. The results are robust if we allow for spatial spillovers a priori. In this setting, we also find robust evidence of positive spillovers leading to growth clusters.
Keywords: C11; C15; C21; R11; O52; 330; model uncertainty; Bayesian Model Averaging (BMA); spatial autoregressive model; determinants of economic growth; urban agglomerations; European regions